THE EFFECT OF DIFFERENT TYPES OF FISH IN THE MAKING OF PEMPEK ON ORGANOLEPTIC CHARACTERISTICS - Steven Ridho Pratama; Tjipto Leksono; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTFish is a food source of animal protein which is very useful for health. As a food ingredient, fish has many advantages over other animal protein sources. The purpose of this study was to determine the effect of different types of fish on the processing of pempek on the organoleptic characteristics produced. The experimental research method conducted an experiment with different types of fish treatment on the quality of pempek, with a non-factorial completely randomized design (CRD) with 4 levels, namely PK = no fish, PN = tilapia PL = catfish PP = catfish, then organoleptic test (test quality of appearance, taste, texture and aroma). The results showed that the effect of different types of fish in the pempek processing on organoleptic characteristics had a significant effect on organoleptic characteristics. The best treatment was (PP) with characteristics of golden yellow appearance (7.32), specific aroma of catfish (7.24), very savory taste (7.32), compact solid texture (7.56). Thus, the effect of different types of fish on pempek processing on organoleptic characteristics can be carried out. Keywords: Characteristics, Influence, Organoleptic, Pempek.